Integration of experiences of contingency in patients with advanced cancer supported by a multimodal art approach - Yvonne Weeseman; Michael Scherer-Rath; Nirav Christophe; Henny Dörr; Mirjam Sprangers; Esther Helmich; Niels van Poecke; Hanneke van Laarhoven (PLoS ONE, 2025)
To support patients with cancer in a palliative treatment phase with the integration of experiences of contingency into their life narrative, we developed a multi-modal approach: In Search of Stories (ISOS). ISOS consists of the following elements: filling out the self-report RE-LIFE questionnaire, drawing of Rich Pictures, and reading an exemplary story with a spiritual counselor, followed by a co-creation process with a professional artist. In the current article we illustrate how patients moved through the process of integration of experiences of contingency during the meetings of ISOS by presenting two case descriptions. All meetings of the first two patients who completed the ISOS project were audio recorded, imported into Atlas-Ti and analyzed by applying a phenomenological approach to deepen our understanding of the patient’s experiences throughout the meetings. The two cases showed distinct differences on how the experience of contingency was dealt with and how the integration of experiences of contingency into the life narrative unfolded. Patients focused on life goals and values concerning connection with loved ones, and on leaving a legacy behind, which was expressed through creating a work of art. The current study provides preliminary insight into how patients can go through a process of integration of experiences of contingency into their life narrative, which could inform the development of future support for patients with advanced cancer dealing with experiences of contingency. Specifically, offering patients possibilities to express themselves through materials within an artistic setting could support these patients to find new words and additional non-linguistic ways of expressing their experiences, and thereby facilitate the integration of experiences of contingency into their life narrative.